Efficient Photocatalytic Hydrogen Generation by Pd Modified La-NaTaO3 Nanoparticle - Husni Husin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The advantage of palladium modified La-doped NaTaO3 (Pd/La-NaTaO3)semiconductor photocatalyst for enhanced hydrogen generation under irradiation at the ultraviolet range has been investigated. The La-NaTaO3 has been synthesized by sol-gel technique. The palladiums are loaded by impregnation of aqueous palladium nitrate solution. The palladium supported of La-NaTaO3 composites are characterized by transmission electron microscopy (TEM), high-resolution HRTEM (HRTEM), and X-ray absorption spectroscopy (XAS). The HRTEM images indicate that Pd nanoparticles (NPs) aredeposited on the surface of La-NaTaO3. Most of the Pd deposits have diameters ranging from 3 to 4 nm. XAS spectra shows that the Pd-La-NaTaO3 absorbance profiles of the pristine and used samples are overlapped with the Pd foil, indicating that oxidation of the fresh and used cocatalyst was identical in nature with that of the palladium foil. Hydrogen production from pure water irradiation with ultra violet (UV) light source is 1.1 mmol g-1h-1 on La-NaTaO3 photocatalysts. The activity of the La-NaTaO3 up to 8.9 mmol g-1h-1 H2 froman aqueous methanol solution are obtained. The hydrogen evolution on the La-NaTaO3 sample can be further increase of 36.49 mmol g-1h-1 or 4.1 times higher by depositing nanosized Pd as a cocatalyst on the surface photocatalyst. The highest hydrogen generation is observed at 0.15 wt% Pd loading. The higher activity of the Pd/tantalates from aqueous methanol solution is attributed to an important suppressing in the electron–hole pairs recombination due to the effect produced by the presence of La in the NaTaO3 structure as well as by the role of methanol acts as hole-trap and Pd like electron-trap.